Genetic diversity of roselle in Guatemala revealed by AFLP markers. - Ponciano-Samayoa, Karla Melina (2012)
Genetic diversity of roselle in Guatemala revealed by AFLP markers. The objective of this study was to characterize a collection of 17 genotypes of roselle that were collected in Guatemala. During July 2010/ May 2011, twelveselective combinations of AFLP were amplified at Instituto de Ciencia y Tecnología Agrícolas (ICTA), to identify clusters and to analyze the genetic diversity within the collection. A 98% of polymorphic loci was observed, nine per amplification in average. Five selective primer pairs were high informative and are recommended for future investigations.No duplicated genotypes were identified. The clustering and correspondence analysis identified three closely related groups. A fourth group included accession 205, characterizedby early maturity and high yield. The clusters formed were similar to those identified in a previous agromorphological characterization. Probably, there is a genetic linkage between AFLPs and quantitative trait loci (QTLs) that can beused in marker-assisted selection. The genetic diversity (Nei) was high (0.3053). The genetic differentiation (GST) between groups was 57.62%. The genetic variability within clusters was lower (42.38%) and probably due to the low genetic flow (Nm=0.3678) commonly found in in breed species.